A novel technique for a rare diagnosis: MRI‐guided vaginal biopsy of Skene gland adenocarcinoma: Pictorial Essay. Issue 6 (9th July 2021) - Dentry, Matt; McBean, Rhiannon; Garrett, Andrea; Brown, Nicholas
Summary: FDG‐PET and MRI imaging of the pelvis identified a suspicious lesion in a patient with a history of small cell neuroendocrine tumour of the vagina, and after a negative surgical biopsy, a multidisciplinary team meeting decided to proceed with MRGB (magnetic resonance‐guided biopsy). The patient remains well and in remission two years after anterior exenteration, with final histology of the lesion determined to be Skene gland adenocarcinoma. MRGB is a novel and effective way to diagnose vaginal lesions.